The Crayons Give Thanks - Daywalt, Drew (ILT)/ Jeffers, Oliver (ILT); Jeffers, Oliver (New York: NY Philomel, 2024)
This laugh-out-loud story starring the Crayons shows readers there are so many things to be thankful for, everywhere we look.
new kids book 2024 fall.
Keywords: Crayons -- Fiction; Colors -- Fiction; Thanksgiving Day -- Fiction; Holidays -- Fiction; Gratitude -- Fiction; Humorous fiction